오장환의 동시세계 연구 - 곽효환(Kwak, Hyo-Hwan) (한국시학연구, 2018)
오장환 시세계의 중요한 특징은 『시인부락』의 순수서정성을 바탕으로 하면서도 『시인부락』이 비판하였던 모더니즘을 전면 부정하지는 않고 양편 모두에 비판적인 자세를 취함으로써 한국시의 순수서정성과 모더니즘이라는 한계를 극복하려는 자세를 보이면서 여러 차례 시적 변신과정을 보이는데 있다. 오장환의 시세계에 대한 평가와 조명은 이와 같이 어느 정도 모아지고 있는데 반해 그의 동시에 관한 논의는 아직 미진하다. 오장환 동시는 안성공립보통학교 재학 중인 11세 때 일본 천황의 즉위를 축하하는 기념호로 제작된 ‘어대전 제9호’에 실린 동시 「밤」(1928년 12월 24일 발행한 안성공립보통학교 학습회 학예부 문집에 수록)을 시작으로 총 51편의 창작동시와 1편의 번역동시를 발표한 것으로 확인된다. 오장환은 1933년 12월 『어린이』에 동시 「눈」을 발표한 것을 출발점으로 1934년 2월 역시 『어린이』에 「바다」, 「기러기」, 「수염」 등 3편을 발표하였다. 이어 1934년 7월부터 1940년 7월까지 『조선일보』에만 총 45편의 동시를 발표하였고 해방 후에 2편의 동시를 더 발표하였다. 이로 미루어 볼 때 오장환의 동시 창작은 시보다 먼저 시작되어 문학적 생애 전체에 걸쳐 지속적으로 창작, 발표되었음을 알 수 있다. 이는 오장환의 동시가 여기로 쓰여 진 것이 아니라 초기 문학세계의 중요한 부분을 차지하고 있다고 할 수 있다. 따라서 오장환의 동시에 대한 체계적이고 깊이 있는 연구는 오장환 시세계와 문학적 생애를 온전히 조명할 수 있게 할 뿐만 아니라 오장환 문학의 중요한 특징으로 꼽히는 시적 편력, 즉 시와 문학관의 변모과정을 살피는 데 있어 중요한 출발점이 될 수 있을 것이다. The important point of Oh Jang-hwan's poetic world is that it is based on the pure lyricism of Siinburak(Poet Village), also it does not entirely denied the modernism which Siinburak had criticized, but it takes a critical attitude to both sides in order to overcome the limit of pure lyricism and modernism by showing numerous times of poetic transformation processes. The evaluation and illumination of Oh Jang-hwan 's poetic world is gathered to some extent, but the discussion on his Children's Poetry is still insufficient. Children's poem of Oh Jang-hwan begins with the children's poem 'Night' which was included in 'Eodaejeon' No.9 a commemorative issue to celebrate the Japan Emperor's enthronement while he was in Ahnsung public primary school at the age of 11, after that he published total 51 creative works of children's poem and 1 translated children's poem. In December 1933 Oh Jang-hwan started to announce the children's poem 'Snow' in Children and in February 1934 'Ocean', 'Goose', 'Beard' was published also in Children. Then, from July 1934 to July 1940, a total of 45 works of children's poems were announced only in Chosun Ilbo and two more children's poem works were announced after liberation. Judging from the fact that Oh Jang-hwan's creation of children's poems began before the poetries, and was constantly created and published throughout the literary career. It means that his children's poems was not written just as some hobby but it is an important part of the early literature world. Therefore, the systematic and in-depth study of Oh Jang-hwan's children's poems will not only provides a complete overview of the poetry world and literary life, but also is an important starting point for examining the poetic wanderings ―the transformer process of poetry and literary prospective. KCI Citation Count: 2